Context Adaptation in Public Administration Change Processes: A Case Within the Swedish Transport Administration - Ekendahl, Paulina; Bäckström, Izabelle; Norrman, Andreas (Scandinavian Journal of Public Administration, 2025)
The purpose of this paper is to explore context adaptation of change processes in the setting of public administration. This is done by adopting a contingency approach. Thus, the research question guiding this study is: How is context adaptation enacted in change processes and what are the behavioural implications? Drawing on empirical findings from the Swedish Transport Administration, the study illustrates the enactment of context adaptation and its behavioural implications through the phases of change. The analysis identifies key contextual factors and contingency variables, demonstrating that context adaptation is enacted by managers and employees. Notably, certain context adaptation led to contradictory behavioural patterns. This study hence contributes to public administration literature by exploring the enactment of context adaption in change processes which represents an understudied phenomenon in this field.